Drug Eluting Stents: Arsenic Trioxide–Coated Stent Is an Endothelium‐Friendly Drug Eluting Stent (Adv. Healthcare Mater. 15/2018). Issue 15 (8th August 2018) - Zhao, Yinping; Du, Ruolin; Zhou, Tian; Yang, Dongchuan; Huang, Yuhua; Wang, Yi; Huang, Junli; Ma, Xiaoyi; He, Fugui; Qiu, Juhui; Wang, Guixue
Abstract : Traditional drug‐eluting stents often delay endothelialization whilst inhibiting intimal hyperplasia. In article1800207 by Juhui Qiu, Guixue Wang, and co‐workers, an arsenic trioxide‐eluting stent effectively facilitates rapid re‐endothelialization whilst preventing in‐stent restenosis. Cover image designed and produced by Jin Yang.